Influence of Light, Soil Nutrients, and Environmental Stress on Plant Growth and Development - Ishaq, Umar (EcoBiotics: Journal of Animal & Plant Sciences, 2025)
Plant science is important in the study of the physiological, biochemical, and molecular processes which are involved in plant growth and adaptation. The research paper provides studies on three key factors that have a serious impact on the productivity of plants, that is, light intensity, the availability of nutrients in soil, and environmental stress conditions. Light is the most important energy source in photosynthesis and it directly influences the morphology of plants, formation of chlorophyll and the biomass of the plant (Zhu et al., 2010). The soil nutrients, including nitrogen, phosphorus, and potassium, control the enzyme activities, the formation of structure and yield potential (Marschner, 2012). Also, the extreme constraints of plant metabolism caused by such abiotic stresses as drought, salinity, and temperature changes cause physiological and genetic responses leading to tolerance (Zhu, 2016). Through combination of recent discoveries made between the years 2000 and 2025, this study will give a complete picture of the interaction of these factors to give superlative plant health and productivity. The research design was a mix of controlled growth study, soil nutrient client and literature-based analysis of stress physiology. The findings indicated that the optimal photosynthetic efficiency is at moderate light intensity (around 3000- 3500 lux), balanced nutrient supply is more effective in increasing the plant vigor, adaptive stress responses increase the resilience of plants to unfavorable conditions. The discussion indicates new developments in molecular breeding, genetic engineering and the sustainable management of soil as the key ways forward to the achievement of global food security amid climate change. This combined discussion reveals the need to merge environmental, physiological and molecular approach to reinforce the basis of the current form of plant science.